Meningkatkan Komunikasi Pemerintah Melalui Digitalisasi Strategis di Indonesia: Peta Jalan untuk Peningkatan Keterlibatan Publik dan Penyampaian Layanan - Pratama Firmansyah, Helmi; Jibrael Rorong, Michael (Prodi Ilmu Administrasi Negara, 2025)
This study aims to analyze the role of strategic digitalization in enhancing government communication in Indonesia, with a focus on improving public engagement and service delivery. Using a descriptive qualitative approach through literature analysis and policy review, the study maps out key strategies such as the optimization of social media, the development of public service portals, the utilization of e-participation platforms, and the provision of interactive and user-friendly digital content. The findings indicate that digital tools, including official government accounts, chatbots, and identity-based service applications, not only accelerate the flow of information but also strengthen transparency and accessibility of public services. Furthermore, online forums, feedback mechanisms, and crowdsourcing initiatives foster greater public participation in the policymaking process. The study concludes that strategic digitalization not only improves government–citizen communication but also provides a roadmap toward responsive, inclusive, and transparent governance in the digital era.